Method to estimate the fatigue-strength scatter of shafts in the high-cycle and very-high-cycle fatigue regimes. (January 2023) - Vetter, Sebastian; Leidich, Erhard; Hasse, Alexander
Highlights: Method to determine the nominal fatigue-strength scatter. Detection of shaft-inherent fatigue-strength scatter and scatter between shafts. Consideration of competing failure mechanisms in the HCF and VHCF regimes. Description of the distribution of non-metallic inclusion size using micro-CT scans. Predictable S-N curve in the HCF and VHCF regimes to avoid failures of shafts. Abstract: The fatigue strength of shafts is subject to scatter. Knowledge of this scatter is essential for producing safe shaft designs. Therefore, this paper investigates the possibility of quantifying the fatigue-strength scatter in the high-cycle and very-high-cycle fatigue regimes. For this purpose, experimental tests were carried out on exemplary shafts to determine the fatigue-strength scatter. A probabilistic model was developed that considers the failure mechanisms of quenched and tempered steels from the surface and the interior. Therefore, the scatter-influencing parameters were statistically modelled. The parameters act as input in local-strength approaches for the failure mechanisms. Using Monte Carlo simulations, shafts can be randomly generated. The shafts so generated are submitted to the approaches for the failure mechanisms by means of finite-element analyses. By statistical evaluation of fictitious nominal stress levels with respect to calculated failures and runouts of the shafts, the probability distribution of the fatigue strength can be determined.